Highways and the environment colloquium held at the Institution of Civil Engineers, London, 4 November 1976. (Institution of Civil Engineers, 1978)
Following on from an introduction by R.J. Bridle, the first session of papers highlight nuisance and measurement in the subject, then progress to identify protective measures and environmental benefits of new roads, and conclude by documenting procedures which evaluate the topic.